Appreciative Inquiry Principles - and Coaching Leaders (2015)
This article, written by Emotional Intelligence Coach Andy Smith, describes the anticipatory principle which is one of the underpinnings of Appreciative Inquiry (AI). It argues that it is easier and more effective to move towards a positive imagined future than away from a negative one. It is principle number 4 in a series of principles outlined. More principle are listed below.